DESIGN OF ROBUST H∞ POWER SYSTEM STABILIZER USING NORMALIZED COPRIME FACTORIZATION - I. Ngamroo; S. Dechanupaprittha (ASEAN Journal on Science and Technology for Development, 2017)
This paper proposes a new design procedure of robust power system stabilizers (PSS) using H∞ control via normalized coprime factorization (NCF) approach. The design procedure of the proposed PSS is systematically described. Moreover, the selection method of the weighting function in H∞ control design is explained in a simple manner. The performance and robustness of the proposed PSS are investigated in comparison with the conventional PSS by examining the case of a single machine connected to an infinite bus (SMIB) system. The simulation results are illustrated to ensure the effectiveness of the proposed PSS.